FAEController: Um Framework de Avaliação de Eficiência Relativa entre Controladores SDN - Klosowski, Eduardo Augusto; Fiorese, Adriano (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
A Software-Defined Network (SDN) requires a controller that is responsible for defining how the network will behave. The controller has the responsibility to install rules to forward data streams through the network devices. Thus, it is necessary that the controller presents performance good enough to attend the network needs. However, with the diversity of existing controllers, some offering more facilities to the developer, while others offer higher performance, a doubt arises regarding which controller manages to attend the network demand, or how much performance can be bargained to get more facilities. To answer these questions, this work presents FAEController. It is an SDN controllers evaluation framework based on relative efficiency obtained by means the Data Envelopment Analysis (DEA) multicriteria decision-making method. This proposed framework takes into account several stages including the controllers' performance evaluation, creation of the performance database and, how to use these database to identify which controllers attend the network demand using the DEA method. Results comprising the proposed framework evaluation indicate the viability of the relative efficiency approach and its relation with the used controllers' resources.